Estratégia de produção e a abordagem da manufatura enxuta: estudos de caso no setor de autopeças brasileiro - Lazarin, Daniel França (2013)
In the 1950s, Japanese companies in the automotive sector, in particular the Toyota Motor Company, began to develop different methods to manufacture vehicles in relation to those used by U.S. industry, known at the time as a system of mass production (OHNO 1997; WOMACK et al. 1992; CUSUMANO, 1989). Breaking this paradigm resulted in a new production model, known as the Toyota Production System (TPS) and popularized in the west by the name of lean manufacturing (LM) or lean production (LP). With the implementation of new production systems, it is generally verified that changes occur in production strategies (PSs), in coordinating the flow of materials and information and also the relationships between customers and suppliers, and these can have major impacts on the ways organizational implemented. Given this context, the main objective of this work is to identify and analyze the relationships between production strategies and lean manufacturing approach in three companies of the auto parts industry that have adopted lean manufacturing as a system for production management, trying to verify the role that STP has in the PSs of each company. We opted for a qualitative approach and the research strategy used was the case study. The results of the study indicate that production strategies and lean production are effectively aligned in the cases studied, showing that LP acts supporting the PS of the companies.